2001
DOI: 10.1108/10650740110386675
|View full text |Cite
|
Sign up to set email alerts
|

Developing webs of significance through communications: appropriate interactive activities for distributed learning environments

Abstract: Interactive activities are an important aspect of distributed learning situations, wherein online communities and learner motivational levels evolve and thrive. Through the thoughtful integration of interactive activities into the online learning process, learners and instructors gain considerable exposure to reciprocally favorable occurrences among learners, content, interface, instructor, community, and self. The thoughtful design and development of a distributed learning environment aids the use of interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 4 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…These activities can be done in or out of a class, as individuals or in groups, with or without technology. According to Crawford (2001), integration of productive interactive activities can develop higher-level thinking skills and can motivate students to complete the online course. Textbook publishers are investing in the enhancement of online education by providing interactive, online activities to accompany their texts.…”
Section: Strategies Used In Online Learningmentioning
confidence: 99%
“…These activities can be done in or out of a class, as individuals or in groups, with or without technology. According to Crawford (2001), integration of productive interactive activities can develop higher-level thinking skills and can motivate students to complete the online course. Textbook publishers are investing in the enhancement of online education by providing interactive, online activities to accompany their texts.…”
Section: Strategies Used In Online Learningmentioning
confidence: 99%
“…Traditional teaching and learning has involved the dictation of notes to students in a face-to-face environment leading to one-way dissemination of knowledge, as well as providing students with assignments expecting feedback on a specified date. This form of teaching and learning has been found to limit interactions between students and lecturers and among the students themselves (Javis, 2012: 59; Crawford, 2001: 68). Furthermore, it has been observed that traditional models have professed the teacher's actions as fundamental to the learning process, the students as passive recipients of knowledge, while knowledge has been viewed as objective – these perceptions have remained dominant in institutions of higher learning (Weinberger and Shonfeld, 2018: 2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This includes learning resources geographically distributed in various locations (Li et al , 2008: 4). Crawford (2001: 68–69) suggest that distributed learning environments (DLEs) eliminate the need for a student to worry about the time and place of study as learning can easily be facilitated using technologies. According to Prieto et al (2014: 9), the combination of virtual learning environments (VLEs) and Web 2.0 tools is what some authors refer to as DLE.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While face-to-face learning environments offer the opportunity to interact on the fly, virtual learning environments must specifically include interactive activities to simulate the learning community involvement that is lacking in the virtual environment. Through participation in these interactive activities, learners are able to fully comprehend the knowledge imparted and develop the higher order thinking skills that are associated with the conceptual nature of the information [17]. To provide these interactive activities and at the same time enjoy the benefits of synchronous online education, some form of support for real-time bidirectional communication can be integrated into the conventional webcast service.…”
Section: Collaboration Systemmentioning
confidence: 99%